1986
DOI: 10.1051/rphysap:01986002107044300
|View full text |Cite
|
Sign up to set email alerts
|

Etude d'un capteur électromagnétique plat de proximité

Abstract: La partie sensible des capteurs de proximité magnétiques est souvent constituée d'une bobine enroulée autour d'un noyau. Nous avons réalisé une bobine dont la géométrie est différente. Elle permet par son incorporation dans un oscillateur, la réalisation d'un capteur de proximité peu coûteux. Nous présentons ici les caractéristiques physiques et électriques de plusieurs échantillons. Cette étude constitue une première approche d'optimisation du capteur et de son électronique associée. Nous montrons que l'on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…=> T C.pS = MTT RHOT .MTS Vs (4) We describe the construction of a triplet, we check that the three point sources are in the same plane; this last is placed at r distance of collocation point: Where R is the distance between point sources i and j: (5) (6) LM TSz _ After we redo the same operations to obtain MTT, the coupling matrix between target point sources Ti them self. Now, we know all parameter values of equation (4), and we can compute flux PT on target.…”
Section: Dpsm Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…=> T C.pS = MTT RHOT .MTS Vs (4) We describe the construction of a triplet, we check that the three point sources are in the same plane; this last is placed at r distance of collocation point: Where R is the distance between point sources i and j: (5) (6) LM TSz _ After we redo the same operations to obtain MTT, the coupling matrix between target point sources Ti them self. Now, we know all parameter values of equation (4), and we can compute flux PT on target.…”
Section: Dpsm Theorymentioning
confidence: 99%
“…A study carried out by [5] showed that the coil in spiral can be assimilated as uniform distribution of current in one case. In this case, the distance between the coil plan and the field measurement point is at least higher than 10 times to the width separating two successive turns of this coil.…”
Section: Sensor Modelingmentioning
confidence: 99%
“…The Laboratoire d'Automatique et de Microélectronique designed a new eddy-current sensor [2]. The theoretical possibilities of this kind of sensor have been studied in [3] and we will not discuss here its effect on the fields generated. It consists of a flat coil carved onto a printed circuit with an epoxy-resin support.…”
Section: The Sensor Specificationmentioning
confidence: 99%
“…De nombreux dispositifs de capteurs de proximité exploitant les courants de Foucault ont été décrits dans la littérature [1][2][3][4]. Dans des articles précédents [5] et [6] nous avons présenté les caractéristiques physiques d'un capteur magnétique de proximité constitué d'une spirale gravée sur un support époxy simple face. Nous avions alors montré que la réponse en fréquence d'un tel capteur était caractéristique d'un modèle inductance-résistance en série.…”
unclassified
“…De façon à améliorer les performances de ce type de capteurs, nous avons réalisé des échantillons gravés en double face, les deux spirales, de caractéristiques géométriques identiques, étant alors enroulées en sens contraire et reliées électriquement par leur centre ; la technique de réalisation de ces capteurs procède des méthodes décrites dans [6]. Il est clair que, par rapport aux capteurs simple face de même géométrie, ces capteurs double face verront leur inductance quadruplée (en admettant un facteur de couplage égal à 1) et leur résistance doublée.…”
unclassified